2011
DOI: 10.1007/s11199-011-9946-z
|View full text |Cite
|
Sign up to set email alerts
|

Older and Younger Adults’ Attitudes Toward Feminism: The Influence of Religiosity, Political Orientation, Gender, Education, and Family

Abstract: The present study explored attitudes toward feminism in 245 U.S. college students and their older relatives. Participants completed a scale of attitudes towards feminism, political orientation, a religiosity measure, and a demographic questionnaire. Results indicated that older adults were more conservative than younger adults on their attitudes towards feminism, religiosity, and political orientation measures. In the young adult sample, attitudes towards feminism were predicted by gender and political orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Regarding the present sample, it needs to be acknowledged that it resulted from willingness of graduate programs to cooperate with the researchers and may thus not be viewed as representative or random. We worked with a sample of young communication scholars—future work may aim to examine whether these effects are more pronounced in a sample of more “senior” scholars who may hold more traditional gender roles attitudes (Bettencourt, Vacha-Haase, & Byrne, 2011). It is desirable to replicate the study with scholars already advanced in their careers, despite likely greater challenges in recruiting participants from this population.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the present sample, it needs to be acknowledged that it resulted from willingness of graduate programs to cooperate with the researchers and may thus not be viewed as representative or random. We worked with a sample of young communication scholars—future work may aim to examine whether these effects are more pronounced in a sample of more “senior” scholars who may hold more traditional gender roles attitudes (Bettencourt, Vacha-Haase, & Byrne, 2011). It is desirable to replicate the study with scholars already advanced in their careers, despite likely greater challenges in recruiting participants from this population.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that this methodological choice would limit our access to older groups of the population. When considering conceptions of gender, compared to older adults, individuals from younger age groups generally hold more varied and inclusive conceptions of gender (Cichy, Lefkowitz, and Fingerman, 2007;Fitzpatrick Bettencourt, Vacha-Haase, and Byrne, 2011). Although not representative of the general public as a whole, researchers may consider conducting more targeted research focusing on this particular demographic, as we inadvertently did with our sample.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Additionally, age of audiences could influence their assessment of news credibility. K E. Bettencourt, K E. Bettencourt, et al 2011 showed that age relates to people's attitudes towards feminism: Younger people have a more positive attitude towards feminism, because the older generation has grown up with more traditional views on gender and family (Livia S. Oláh, Irena E. Kotowska and Rudolf Richter 2018). Several other studies yielded a similar conclusion (F H. Dambrot, M E. Papp and Cheryl Whitmore 1984; Janet T. Spence and Robert L. Helmreich 1979).…”
Section: Hypothesesmentioning
confidence: 99%